Analisis Program Merdeka Belajar dalam Meningkatkan Kualitas Pendidikan - Afriani Abubakar; Abu Bakar; Aulya Azizah; Mutyara (Institusi Agama Islam Negeri (IAIN) Bone, 2025)
This study seeks to understand how the Freedom of Learning Program is being used to make education better at SMPN 2 Watampone. Data was gathered through interviews, documents, and research papers, using a method that describes qualities rather than numbers. The study found that putting Freedom of Learning into practice involves key steps like finding students' skills and interests to help them grow, using projects to teach in ways that boost creativity and self-reliance, using digital tools even with limited resources, and making extracurriculars stronger to help students build character and skills. Also, when teachers and students work together to plan what is taught, students get more involved and feel more responsible for their learning. However, there are issues like not having enough equipment, some students not caring about extracurriculars, and some people not wanting to change how they learn. The study suggests it is important to improve facilities, keep training teachers, and better convince students and parents to get more involved. In general, the Freedom of Learning Program is helping to improve education, but it still needs improvements and changes to fit the school's specific needs.